SPE Annual Technical Conference and Exhibition 1994
DOI: 10.2118/28486-ms
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wellbore Hydraulics on Pressure Behavior and Productivity of Horizontal Gas Wells

Abstract: The objective of this study is to investigate the effect of wellbore hydraulics on the pressure behavior and productivity of horizontal gas-wells. The semi-analytical model used to investigate the effect of wellbore hydraulics, couples gas flow in the reservoir and in the wellbore by utilizing the real gas-pseudopressure function. Pressure and flux distributions along the well are investigated. Conditions under which wellbore hydraulics manifests its effect on the pressure behavior and the productivity of hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Permeability heterogeneity along a horizontal wellbore will cause a high rate of fluid inflow from the reservoir into the wellbore at high-permeability intervals, resulting in an early water break through occurring during these intervals. On the other hand, the pressure drop shows a high value at the heel of horizontal well bores [1,2], This also leads to a higher inflow rate at the heel and an early water breakthrough. The drawdown of oil by means of horizontal wells has many advantages over conventional oil recovery techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Permeability heterogeneity along a horizontal wellbore will cause a high rate of fluid inflow from the reservoir into the wellbore at high-permeability intervals, resulting in an early water break through occurring during these intervals. On the other hand, the pressure drop shows a high value at the heel of horizontal well bores [1,2], This also leads to a higher inflow rate at the heel and an early water breakthrough. The drawdown of oil by means of horizontal wells has many advantages over conventional oil recovery techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses confirmed previous results that the angle of the perforations 90 degrees is better than the test angles 0, 120, and 180 degrees, but it produces greater amounts of inflow through the perforations. Subsequently, others [2][3][4][5] continued their research, and they proposed different coupling models of well flow and perforation into the reservoir. However, in some case studies, only the friction component is observed to study the pressure drops across the wellbore.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the pressure drop of wellbore variable mass flow consists of friction pressure drop, acceleration pressure drop and mixture pressure drop. However, the existing studies on pressure drop of horizontal wells have concentrated on the friction pressure drop and the acceleration pressure drop of the variable mass flow in the horizontal wellbore [4][5][6][7][8][9][10][11][12][13], failing to consider the additional impact of radial inflow on the wellbore flow. Below is a brief overview of the previous research into the variable mass flow in horizontal wells.…”
Section: Introductionmentioning
confidence: 99%